Effect of solidity on aerodynamic forces around straight-bladed vertical axis wind turbine by wind tunnel experiments (depending on number of blades). (October 2016) - Li, Qing'an; Maeda, Takao; Kamada, Yasunari; Murata, Junsuke; Shimizu, Kento; Ogasawara, Tatsuhiko; Nakai, Alisa; Kasuya, Takuji
Abstract: The prediction of aerodynamic forces around straight-bladed Vertical Axis Wind Turbines (VAWT) is important for wind turbine applications. This paper focused on evaluating the aerodynamic forces acting on a single blade, depending on the different numbers of blades in wind tunnel experiments. In this study, numbers of blades were from two to five and the cross-sectional shape of the tested airfoil was a NACA0021. Firstly, the power coefficient was measured by a torque meter and a six-component balance. Secondly, pressures acting on the surface of rotor blades were measured during rotation by multiport pressure devices. Then, the evolutions of normal coefficient, tangential coefficient and lift-to-drag ratio C L /C D, which were obtained from pressure distributions, were discussed. Finally, the power coefficients calculated by pressure distributions were compared with the experiment data of the torque meter and the six-component balance. The results showed that the pressure difference substantially decreased with the increase of solidity. In addition, the values of six-component balance and torque meter showed smaller values than those calculated by pressure distributions. In words, these results provided theoretical significance towards the development of a simple design for straight-bladed VAWT. Graphical abstract: The evaluation of tangential coefficient, normal coefficient, lift coefficient, drag coefficient, power and torque performance at four different solidities were investigated. In order to verify the aerodynamic forces characteristics of the straight-bladed VAWT, pressure distribution on the surface of the rotor blades were measured by multiport pressure devices during rotation in wind tunnel experiments. Moreover, the fluctuations of the power coefficient were compared by the six-component balance, pressure distribution and torque meter, respectively. Highlights: The effects of solidity σ on wind turbine performance were investigated. Power and torque coefficients were compared by torque meter, pressure distributions and six-component balance. The pressure difference substantially decreased with the increase of solidity σ. The values of six-component balance were closer to the values of the torque meter.